Effectiveness and safety of traditional Chinese medicines for non-alcoholic fatty liver disease: Protocol for systematic review and meta-analysis. Issue 25 (19th June 2020) - Qin, Manman; Yuan, Fuqiang; Ren, Jiankun; Chi, Zhenhai
Abstract: Background: Previous reviews indicate that the effect of Traditional Chinese medicines (TCM) on non-alcoholic fatty liver disease (NAFLD) remains uncertainty. The study results published in the past 8 years may change this situation, but there is no updated systematic review. Therefore, we designed this study to systematically evaluate the effectiveness and safety of TCM in the treatment of NAFLD. Methods and analysis: We will search nine online databases from inception to October 01 2019, and the language will not be restricted on included trials. Randomized controlled trials that included patients with NAFLD receiving TCM therapy versus a control group will be included. Two researcher will perform independently the selection of studies, risk of bias assessment and data extraction. We will use the RevMan V.5.2 software with fixed effects model or random effects model according to the heterogeneity test to conduct the data synthesis. We will present the dichotomous data and the continuous data with risk ratios with 95% CIs and weighted mean differences or standardized mean differences with 95% CIs. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system will be used to evaluate the evidence quality with low risk, unclear risk, and high risk. Results: This study will demonstrate an evidence-based review of TCM for NAFLD. Conclusion: The study will provide clear evidence to assess the effectiveness and side effects of TCM for NAFLD. Abstract : Supplemental Digital Content is available in the text